Multinational corporations in violent conflict: a case study of firestone in Liberia - Gough, Rebecca (Department of Political Studies, 2019)
The First Liberian Civil War began with an insurgency led by Charles Taylor on Christmas Eve in 1989. At the time, the company Firestone Liberia (one of many of the subsidiaries of the multinational, Bridgestone Corporation) had been operating the world’s largest rubber plantation in Liberia’s Margibi County for over six decades. Over the course of three years, Firestone engaged with various actors in the Liberian conflict theatre in order to continue operating its rubber plantation. The most notable of these actors was the warlord, Charles Taylor, a relationship for which Firestone Liberia has received much criticism. This case study is situated within the broader debate on the role of multinational corporations in host countries that descend into conflict. The existing literature on the topic exposes a potentially ambivalent role for private actors as either catalysts for aggravating conflict dynamics or promoters of peace within conflict zones. This research contends that insufficient attention has been paid to understanding the minutiae of corporate behaviour in contemporary conflict and that more in-depth low-n case studies are required before prescribing a positive role for companies in conflict zones. The findings of this paper reveal the importance of accounting for variables, such as conflict characteristics and geo-economic and geopolitical conditions, and how these limit the agency of private actors in situations of violent conflict.